1999
DOI: 10.1038/7391
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive immunization with the Pseudomonas V antigen protects against type III intoxication and lung injury

Abstract: Pseudomonas aeruginosa is an opportunistic bacterial pathogen that can cause fatal acute lung infections in critically ill individuals. Damage to the lung epithelium is associated with the expression of toxins that are directly injected into eukaryotic cells through a type Ill-mediated secretion and translocation mechanism. Here we show that the P. aeruginosa homolog of the Yersinia V antigen, PcrV, is involved in the translocation of type III toxins. Vaccination against PcrV ensured the survival of challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
353
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(371 citation statements)
references
References 38 publications
17
353
1
Order By: Relevance
“…4,5 These proteins alter the function of the host cell, assist the microbe to invade, resist phagocytosis, grow in deep tissues and cause disease. [6][7][8][9][10] The T3SS is involved in a range of pathogenic mechanisms and its activity correlates closely with disease progression and outcome. 11 The well-studied plasmid-encoded Ysc of Yersinia is representative of these common virulence systems.…”
mentioning
confidence: 99%
“…4,5 These proteins alter the function of the host cell, assist the microbe to invade, resist phagocytosis, grow in deep tissues and cause disease. [6][7][8][9][10] The T3SS is involved in a range of pathogenic mechanisms and its activity correlates closely with disease progression and outcome. 11 The well-studied plasmid-encoded Ysc of Yersinia is representative of these common virulence systems.…”
mentioning
confidence: 99%
“…In a previous study, it was shown that administration of anti-PcrV antibody (Ab) was able to block the translocation of P. aeruginosa type III-secreted toxins [7]. Anti-PcrV immunoglobulin (Ig)G also exerted therapeutic effects, reducing septic shock and mortality in an animal model of acute P. aeruginosa infection [7,8]. However, the efficacy of anti-PcrV IgG in chronic P. aeruginosa infection has not yet been clarified.…”
mentioning
confidence: 99%
“…Expression of these toxins causes epithelial injury and inhibits the host immune response [3,[5][6][7]. PcrV is homologous to the Vantigen (LcrV) found on the surface of Yersinia and appears to be an integral component of the translocation process [7]. In a previous study, it was shown that administration of anti-PcrV antibody (Ab) was able to block the translocation of P. aeruginosa type III-secreted toxins [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations